Potensi Antiinflamasi Ekstrak Etanol Daun Sawo Kecik (Manilkara kauki L.) - Aminah Syarifuddin; Debi Dinha Octora; Cucu Arum Dwi Cahya (Jurnal Indah Sains dan Klinis, 2022)
Background: Inflammation often occurs in the community in the joints, its prevalence in the world is around 11.9 million. The prevalence in high-income countries is around 1.3 million, while in low-income countries it reaches 5.9 million, Southeast Asia has 4.4 million. Objective: The study was directed to test the anti-inflation effect of EDSK. Method: The method causes oedema of the soles of the test animals through carrageenan induction. The EDSK test as an anti-inflammatory was used by 25 animals distributed in 5 groups; one positive and one negative control, and 3 treatments each of SND, CMC, SEDSK1, SEDSK2, SEDSK3. Results: The percentage of inflammation in the five groups decreased continuously starting from the first hour to the 6th hour after carrageenan induction. The largest percentage of inflammation occurred at the 2nd hour in CMC, followed by SEDSK1, SEDSK2, SEDSK3 and SND. The greatest percent inhibition was SND, followed by SEDSK3, SEDSK2, and SEDSK1. The best inhibition was on SEDSK3 after SND, followed by SEDSK2, and SEDSK1.Conclusion: Research provides information that the SEDSK1, SEDSK2, and SEDSK3 groups have potential anti-inflammatory agents.